STRATEGI KOMUNIKASI KEPALA DESA DALAM MEMBENTUK CITRA POSITIF DI DESA SILIBATA-BATA KECAMATAN ARU TENGAH KABUPATEN ARU - Demsy Wattimena; Charles Johandersson Tiwery; Nela Unenor (JURNAL BADATI, 2023)
The research aims to identify and analyze the village head's communication strategy in forming a positive image of the community in Selibata-Bata village. In this study the data collection technique used was interviews, observation and documentation. receive support from the community, but if the village head does not receive support because he has a negative image, the village head must have a good communication strategy so that he can again persuade and invite the community to implement and participate in whatever program he is doing. The formation of a positive image among the community depends on how the village head relates to managing the strategy so that later this strategy is able to restore a positive image to government institutions in the community. The communication strategy used by the village head to regain the trust of the community is to build good face-to-face communication formally. Village head communication with the community needs to use communication media both verbally and non-verbally, both directly and online.